Siderophore Scaffold as Carrier for Antifungal Peptides in Therapy of Aspergillus fumigatus Infections - Joachim Pfister; Roland Bata; Isabella Hubmann; Anton Amadeus Hörmann; Fabio Gsaller; Hubertus Haas; Clemens Decristoforo (Journal of Fungi, 2020)
Antifungal resistance of human fungal pathogens represents an increasing challenge in modern medicine. Short antimicrobial peptides (AMP) display a promising class of antifungals with a different mode of action, but lack target specificity and metabolic stability. In this study the hexapeptide PAF26 (Ac-dArg-dLys-dLys-dTrp-dPhe-dTrp-NH2) and the three amino acid long peptide NLF (H2N-Asn-Leu-dPhe-COOH) were coupled to diacetylfusarinine C (DAFC), a derivative of the siderophore triacetylfusarinine C (TAFC) of Aspergillus fumigatus, to achieve targeted delivery for treatment of invasive aspergillosis. Conjugated compounds in various modifications were labelled with radioactive gallium-68 to perform in vitro and in vivo characterizations. LogD, serum stability, uptake- growth promotion- and minimal inhibitory concentration assays were performed, as well as in vivo stability tests and biodistribution in BALB/c mice. Uptake and growth assays revealed specific internalization of the siderophore conjugates by A. fumigatus. They showed a high stability in human serum and also in the blood of BALB/c mice but metabolites in urine, probably due to degradation in the kidneys. Only PAF26 showed growth inhibition at 8 µg/ml which was lost after conjugation to DAFC. Despite their lacking antifungal activity conjugates based on a siderophore scaffold have a potential to provide the basis for a new class of antifungals, which allow the combination of imaging by using PET/CT with targeted treatment, thereby opening a theranostic approach for personalized therapy.